Riesen in der Literatur des Mittelalters Diskursive Formationen im deutschen Sprachraum - van Beek, Alan Lena (Archivum Medii Aevi Digitale - Studies: Theses, 2021)
This book investigates divergent conceptions of giants in medieval textual traditions. The focus is on Middle High German and Latin texts with occasional excursions into Scandinavian and English studies. The methodological approach consists of a combination of historical discourse analysis and historical anthropology. The juxtaposition of knowledge orders and discursive formations is studied from about 800 to about 1600 on the basis of significant texts, pictorial representations and material evidence. The reflection of the concepts of giants is thematically structured according to the biblical, encyclopedic and legendary tradition, the reception of antiquity and heroic epic, as well as genealogical aspects and the question of the giants' status of truth in the Middle Ages.